2018
DOI: 10.1002/uog.17528
|View full text |Cite
|
Sign up to set email alerts
|

Maternal arterial stiffness and fetal cardiovascular physiology in diabetic pregnancy

Abstract: Arterial stiffness is higher in pregnant women with diabetes than in controls. Fetuses of diabetic mothers show altered cardiovascular parameters, with higher AoV-VTI and lower LV-MPI, which are markers of myocardial function. Placental function assessed by UA-RI was normal despite differences between groups. Arterial stiffness did not correlate with placental or fetal cardiovascular variables. Instead, the findings are likely to represent a shared response to the environment of abnormal glucose metabolism. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
0
18
2
Order By: Relevance
“…In a prospective study conducted by Moodley et al, it was shown that pregnant women with pregestational and gestational diabetes mellitus had more arterial stiffness compared to non-diabetic pregnant women, but this variability did not cause a deterioration in placental or fetal cardiovascular parameters. [32] In our study, no difference was found between the two groups in terms of arterial stiffness. The reason for not showing a difference between the study and control groups in terms of arterial stiffness may be that the cardiovascular evaluation of the patients with gestational diabetes mellitus was performed as soon as they were diagnosed.…”
Section: Discussioncontrasting
confidence: 60%
“…In a prospective study conducted by Moodley et al, it was shown that pregnant women with pregestational and gestational diabetes mellitus had more arterial stiffness compared to non-diabetic pregnant women, but this variability did not cause a deterioration in placental or fetal cardiovascular parameters. [32] In our study, no difference was found between the two groups in terms of arterial stiffness. The reason for not showing a difference between the study and control groups in terms of arterial stiffness may be that the cardiovascular evaluation of the patients with gestational diabetes mellitus was performed as soon as they were diagnosed.…”
Section: Discussioncontrasting
confidence: 60%
“…To our knowledge, this is the first study looking comprehensively at biventricular function and utilizing speckle-tracking assessment. Obesity in pregnancy is a strong risk factor for the development of hypertensive disorders of pregnancy, fetal growth restriction and gestational diabetes, all of which have been shown to be associated with significant deficits in maternal cardiovascular function [28][29][30][31][32][33] . By excluding from our prospective study obese women who developed these complications, we may have inadvertently introduced exclusion bias by not studying obese women who developed cardiac dysfunction as a consequence of these pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Moodley et al. 44 interestingly noted that maternal arterial stiffness is increased in pregestational and gestational diabetic mothers and although this did not correlate with the altered fetal cardiovascular assessments, the authors hypothesized that these findings might show a shared response to the metabolic changes in diabetes. Our cohorts were similar in that the mothers had relatively tight glucose control for diabetes patients and their cohort did not include large for gestational age babies or have obvious evidence of placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%